Analisis Literatur Terhadap Program Keluarga Harapan Sebagai Instrumen Pemenuhan Hak Ekonomi Dan Budaya Dalam Perspektif HAM Generasi Kedua Di Lombok Timur - Jailani, Muhammad; Islam, M. Hotibul (Universitas Mataram, 2025)
This article presents a literature analysis of the Family Hope Program (PKH) as an instrument for fulfilling economic and cultural rights within the framework of second-generation Human Rights (HAM) in East Lombok. Second-generation human rights include the rights to work, education, health, and cultural participation that must be fulfilled by the state through fair and measurable policies. Through a systematic literature review approach to national scientific publications, this study evaluates the relationship between policy formulation, legal regulations, and implementation of PKH with the principles of economic and cultural rights. The results of the study indicate that normatively PKH has been designed to fulfill aspects of second-generation human rights, especially through facilitating access to basic services for the poor. However, implementation at the local level such as East Lombok has not fully reflected a human rights-based approach, especially in terms of recognizing local cultural values ​​and community participation. This finding emphasizes the importance of reformulating PKH policies to be more contextual, inclusive, and rights-based in their implementation in the regions.